Rematerial: from waste to architecture - Bahamón Ríos, Alejandro. 1972-
Everyday, millions of tons of garbage are dumped into landfills and consigned to perpetual disuse. But when creativity meets resourcefulness, waste can become the material for building. Never before in history has the impact of man on this planet been so important. The construction industry is one of the most polluting in the world, so contemporary architects can play a fundamental role by using waste, and-what's more, ingenuity-to convert it into structures that are useful, imaginative, and beautiful. In our society, garbage is considered filthy, and we want only to hide it from sight. Rematerial features projects that rescue discarded materials from paper cups to cargo containers and transform them into imaginative, attractive, efficient buildings and projects that are sustainable, innovative, even daring from a conventional perspective. Rematerial brings to light a movement of diverse professionals from around the world who address this fundamental theme: the reuse of materials with architectonic purpose. Though the results are as varied as the designers, all their proposals stem from the intention of giving new life to what had been thrown out. Complementing the built work shown here, the book presents a series of initiatives aimed at promoting the use of waste in architecture, and articles that illustrate a wide panorama of the contemporary recycling culture.